Robotic Transanal Total Mesorectal Excision Compared to Laparoscopic Transanal Total Mesorectal Excision: Oncologic Results of the Past 5 Years - Coco, Danilo; Leanza, Silvana (Open Access Macedonian Journal of Medical Sciences, 2022)
Colorectal cancer is one of the deadliest diseases on the planet. Rectal cancer (RC) is the 8 th most common type of cancer disease worldwide, accounting for over 300,000 fatalities in 2018. Total mesorectal excision (TME) is considered as the gold standard approach for surgical RC management. To alleviate technical problems associated with dissection of distal rectal, transanal procedure to mesorectum was developed. The robotic operating platforms’ development has brought about the most significant change. The robotic method, which was described first in the year 2001, is gaining popularity in colorectal surgery. A stable camera platform with three-dimensional imaging and tremor filtering, motion scaling, instruments with numerous degrees of freedom, 3 rd arm for fixed retraction, ambidextrous capability, superior ergonomics, and less fatigue, all these advantages have all influenced robotics implementation. However, there are certain disadvantages to robotic surgery, such as high expenses, lengthy time of operation, a bulky cart, and absence of haptic sense. Robotic transanal TME (R-TA TME) is unique method that integrates potential advantages of perineal dissection with precise control of distal margins, along with all robotic technology advantages with respect to dexterity and greater precision. This review goal is to evaluate the available literature critically regarding R-TA TME in comparison to laparoscopic TA TME (L-TA TME) using the most prevalent histopathological metrics, which are the circumferential resection margin, the distal rectal margin, recurrence rate, specimen quality, advantages, and disadvantages. Oncological results for the past 5 years were used. The resources were obtained from electronic sources such as Google Scholar and PubMed. The conclusion of this review revealed that R-TA TME is as safe as well as feasible as L-TA TME, is technically possible, and has comparable oncological results and short-term post-operative outcomes. However, further investigation is required to evaluate long-term oncological or functional results.